Peritoneal dialysis practice in Australia and New Zealand: A call to sustain the action. Issue 7 (July 2016) - Mudge, David W; Boudville, Neil; Brown, Fiona; Clayton, Philip; Duddington, Michelle; Holt, Stephen; Johnson, David W; Jose, Matthew; Saweirs, Walaa; Sud, Kamal; Voss, David; Walker, Rowan
Abstract: This paper updates a previous 'Call to Action' paper ( Nephrology 2011 ; 16: 19–29) that reviewed key outcome data for Australian and New Zealand peritoneal dialysis patients and made recommendations to improve care. Since its publication, peritonitis rates have improved significantly, although they have plateaued more recently. Peritoneal dialysis patient and technique survival in Australian and New Zealand have also improved, with a reduction in the proportion of technique failures attributed to 'social reasons'. Despite these improvements, technique survival rates overall remain lower than in many other parts of the world. This update includes additional practical recommendations based on published evidence and emerging initiatives to further improve outcomes. Summary at a Glance: This paper updates the situation of PD in ANZ since the call to action paper in 2011. It subsequently reviews what are the measures available in the current literature to sustain this action in improving outcomes in PD patients in the ANZ population.